2016
DOI: 10.1111/xen.12236
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet sequestration and activation during GalTKO.hCD46 pig lung perfusion by human blood is primarily mediated by GPIb, GPIIb/IIIa, and von Willebrand Factor

Abstract: Background Here we ask whether platelet GPIb and GPIIb/IIIa receptors modulate platelet sequestration and activation during GalTKO.hCD46 pig lung xenograft perfusion. Methods GalTKO.hCD46 transgenic pig lungs were perfused with heparinized fresh human blood. Results from perfusions in which αGPIb Fab (6B4, 10mg/L blood, n=6), αGPIIb/IIIa Fab (ReoPro, 3.5mg/L blood, n=6), or both drugs (n=4) were administered to the perfusate were compared to 2 additional groups in which the donor pig received DDAVP, 3μg/kg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 46 publications
(65 reference statements)
1
53
0
Order By: Relevance
“…In addition, others have reported platelet activation and sequestration become attenuated when desmopressin is administered to pigs prior to lung procurement to deplete pig vWF . Alternatively, Burdorf L et al recently showed the important role of anti‐GPIb Ab therapy on reducing lung xenograft injury that could be a potential additive treatment to inhibit platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, others have reported platelet activation and sequestration become attenuated when desmopressin is administered to pigs prior to lung procurement to deplete pig vWF . Alternatively, Burdorf L et al recently showed the important role of anti‐GPIb Ab therapy on reducing lung xenograft injury that could be a potential additive treatment to inhibit platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…96 GPIb blockade proved insufficient to prevent platelet activation and sequestration in pig livers perfused with human blood, 97 but a combination of GpIb and GpIIb/IIIa blockade successfully prevented platelet sequestration. 98 Pre-infusion of 1-deamino-8-d-arginine vasopressin to the donor pig reduced vWF content in the lung graft to attenuate platelet activation and complement/coagulation activation. 99 α-1-Antitrypsin, a circulating anti-inflammatory glycoprotein, inhibited proteases released by inflammatory cells, especially neutrophils, to attenuate xenograft rejection.…”
Section: Pharmacolog Ic Interventionsmentioning
confidence: 99%
“…The fusion protein, GpVI‐CD39, effectively delayed vascular thrombosis without a risk of bleeding . GPIb blockade proved insufficient to prevent platelet activation and sequestration in pig livers perfused with human blood, but a combination of GpIb and GpIIb/IIIa blockade successfully prevented platelet sequestration . Pre‐infusion of 1‐deamino‐8‐d‐arginine vasopressin to the donor pig reduced vWF content in the lung graft to attenuate platelet activation and complement/coagulation activation .…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%
“…Burdorf et al showed that platelet sequestration and activation during GTKO.hCD46 pig lung perfusion by human blood was primarily mediated by GPIb, GPIIb/IIIa, and von Willebrand Factor [22]. Laird et al showed that transgenic expression of human leukocyte antigen (HLA)-E attenuates GTKO.hCD46 pig lung xenograft injury [23].…”
Section: Introductionmentioning
confidence: 99%